ChemInform Abstract: Transparency Through Structural Disorder: A New Concept for Innovative Transparent Ceramics. Issue 13 (March 2015) - Al Saghir, Kholoud; Chenu, Sebastien; Veron, Emmanuel; Fayon, Franck; Suchomel, Matthew; Genevois, Cecile; Porcher, Florence; Matzen, Guy; Massiot, Dominique; Allix, Mathieu
Abstract Highly transparent polycrystalline glass ceramics of composition Sr1+x/2Al2+xSi2‐xO8 (0 < x ≤ 0.4) are prepared by melt quenching of stoichiometric amounts of SrCO3, Al2O3, SiO2 (Rh/Pt crucible, 1.